SIMULASI RANGKAIAN SEVEN SEGMENT MENGGUNAKAN MULTISIM PADA PEMBELAJARAN RANGKAIAN ELEKTRONIKA ANALOG DAN DIGITAL DI SMKS INFORMATIKA SUKMA MANDIRI - Ahmad Surahmat; Tb Dedy Fu’ady (Journal of Innovation And Future Technology (IFTECH), 2020)
Electronic components are the most complex and sensitive components, not infrequently damage occurs if the components used are not appropriate, for example, excess power, current, short and others. Therefore simulation software can help the process of designing electronic circuits before being patented directly on the components. Not only that, we can also use electronic devices that we cannot reach (buy and meet) like the oscilloscope in the simulation software. The use of a simulation device is used one of them to build a concept in terms of teaching and learning. NI Multisim 11.0 software can be used in the teaching and learning process in this case is the subjects of a series of analog and digital electronics on the seven segment material. Seven segment is a display that is formed from 7 groups of LED (Light Emitting Diode) segments that function to emit light when passing through an electric current through which it is arranged in such a way as to form numbers from 0 (zero) to 9 (nine). Where in this simulator there is a simulation that shows the process of the formation of hex numbers as output. This research discusses how to design schematic circuits, analyze, simulate, check errors, and make layouts on a PCB. The results of this study concluded that the use of Multisim NI software is very good for learning media so that the material presented will be easier to understand.